TINJAUAN DESAIN MASKER VALVE UNTUK PENGGUNAAN NONMEDIS DALAM KONDISI PANDEMI - Musdah Mulia Mukmin (Universitas Mercu Buana, 2021)
The Covid-19 pandemic which occurred during early 2020 has spawned a new habit for society, called the New Normal. One of these new habits is the use of masks when we are going outside. This new habits cause emergence new variant of mask which inspired by the non-medical use mask, one of which is valve masks. Valve masks are becoming more and more prevalent as this new habits develops. This inspired the author to conduct a review of the valve mask design, the work system of this product, as well as its weaknesses and advantages. Due to this reasons, the author uses a descriptive method in conducting a review of this product. The author selects several samples that represent each type of valve mask. The results of this study indicate that in general, there are three types of valve mask variants, which are one valve mask, two valve mask, and three valve mask. In principle, the valve working system flows the air unidirectional, thus allowing the regulation of circulating air circulate according to the valve position on the mask. Valve masks are relied on in reducing the incidence of tightness compare to the use of usual mask (masks without valves), but on the other hand, the valve have potential to be an entry and exit door for the Covid-19 virus droplets.